2012
DOI: 10.5194/acp-12-5523-2012
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight SOA formation during limonene ozonolysis: insights from ultrahigh-resolution FT-ICR mass spectrometry characterization

Abstract: The detailed molecular composition of laboratory generated limonene ozonolysis secondary organic aerosol (SOA) was studied using ultrahigh-resolution Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry. Approximately 1200 molecular formulas were identified in the SOA over the mass range of 140 to 850 Da. Four characteristic groups of high relative abundance species were observed; they indicate an array of accretion products that retain a large fraction of the limonene skeleton. The identified … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
134
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(158 citation statements)
references
References 40 publications
19
134
3
2
Order By: Relevance
“…Using the above values for molecular weight, density and van't Hoff factor as input the estimated values of κ i becomes: κ SOA = 0.1265 for SOA, κ POA = 0 for POA and κ BC = 0 for the soot core, respectively. The calculated κ SOA value is similar as reported in the literature for isoprene-derived secondary organic material particles (κ = 0.12 ± 0.06; Kuwata et al, 2013, and references therein), laboratory smog chamber SOA from trimethylbenzene (κ ≈ 0.04-0.15; Jimenez et al, 2009), κ values of SOA formed from m-xylene and toluene (κ ≈ 0.1-0.27; Lambe et al, 2011) and photochemically aged diesel soot particles (κ = 0-0.13; Tritscher et al, 2011).…”
Section: Ccn Activation Modellingsupporting
confidence: 87%
See 1 more Smart Citation
“…Using the above values for molecular weight, density and van't Hoff factor as input the estimated values of κ i becomes: κ SOA = 0.1265 for SOA, κ POA = 0 for POA and κ BC = 0 for the soot core, respectively. The calculated κ SOA value is similar as reported in the literature for isoprene-derived secondary organic material particles (κ = 0.12 ± 0.06; Kuwata et al, 2013, and references therein), laboratory smog chamber SOA from trimethylbenzene (κ ≈ 0.04-0.15; Jimenez et al, 2009), κ values of SOA formed from m-xylene and toluene (κ ≈ 0.1-0.27; Lambe et al, 2011) and photochemically aged diesel soot particles (κ = 0-0.13; Tritscher et al, 2011).…”
Section: Ccn Activation Modellingsupporting
confidence: 87%
“…The mean molar mass (M) is a difficult property to measure, as pointed out by Hallquist et al (2009). In the literature a variety of average molar mass (M) for both SOA (∼ 0.15-0.480 kg mol −1 ; Hallquist et al, 2009;Kuwata et al, 2013) and POA (0.25-0.7 kg mol −1 for lubrication oil; e.g. Stubington et al, 1995) are reported.…”
Section: Ccn Activation Modellingmentioning
confidence: 99%
“…According to several studies SOA particles may contain oligomers, polymers and other high molecular weight molecules (Tolocka et al, 2004;Gao et al, 2004;Kalberer et al, 2004;Hallquist et al, 2009;Hall IV and Johnston, 2011;Kundu et al, 2012). Such oligomers and polymers are likely to affect the phase state of SOA particles.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed the production of many BVOCs appears species (even genotype) and condition specific (Llusia et al 2002;Yuan et al 2009). One study found that a seedling of Scots pine (Pinus sylvestris) emits at least 20 distinct monoterpenes (Heijari et al 2011) and just one of these, limonene, can become over one thousand distinct compounds in the atmosphere (Kundu et al 2012;Holopainen and Blande 2013). Our ability to detect and distinguish these compounds is improving: for example, one study over just one citrus orchard in the USA detected and tracked the varying atmospheric abundance of over 500 different organic compounds derived from the vegetation (Park et al 2013).…”
Section: Condensationmentioning
confidence: 99%